Role of sports marketing in achieving competition among the Iraq sport clubs - Fadhil Mosleh, Mohammed; Mahmoud Shehadeh, Othman; Yousef, Widad (International Journal of Psychosocial Rehabilitation, 2020)
Sports marketing is an important part of the financial activities carried out by sports institutions and clubs. It is generally considered one of the most important recourses on which the economies of some of the developed countries are based. The present study aims to identify the role of sports marketing in achieving the competitive feature of the Iraqi sports clubs. To achieve this, two hypotheses are set: (1) there is a correlation between sports marketing and the competitive feature of the Iraqi sports clubs and (2) sports marketing plays a role in achieving the competitive feature of the Iraqi sports clubs. The research sample includes a random selection of (60) members of the administrative staff of sports clubs in Iraq through the period from October 2, 2019 till December 17, 2019. As for the study tools and instruments, an experimental method (questionnaire with the descriptive method) is used to collect the data. In this regard, the researchers have adopted the marketing scale previously prepared. The second tool includes the construction of the distinctive performance scale. The scientific principles of the two forms have been done in addition to carrying out the pilot study followed by the main experiments of the study sample that consists of (60) individuals. Then, the data are statistically treated by using the (SPSS) program and the obtained results show that there is a correlation between the sports marketing and the competitive feature of sports clubs with a value of (0,849). Thus, sports marketing has a great role in the competitive feature in sports clubs. Besides, it is concluded that there is a strong correlation between sports marketing and the distinctive performance of workers in sports clubs. Finally, the researchers highly recommend the adoption of sports marketing in all the Iraqi sports clubs which would in turn reflected in the distinctive performance of the sports clubs.